Using 77Se-Labelled Foliar Fertilisers to Determine How Se Transfers Within Wheat Over Time - Ramkissoon, Chandnee; Degryse, Fien; Young, Scott; Bailey, Elizabeth H.; McLaughlin, Michael J. (Frontiers in Nutrition, 2021)
Foliar Se fertilisation has been shown to be more efficient than soil-applied fertilisation, but the dynamics of absorption and translocation have not yet been explored. An experiment was undertaken to investigate time-dependent changes in the absorption, transformation and distribution of Se in wheat when 77Se-enriched sodium selenate (Sefert) was applied to leaves at a rate of 3.33 µg Se per kg soil (equivalent to 10 g ha-1) and at two growth stages – stem elongation, Zadoks stage 31/32 (GS1) and heading stage, Zadoks stage 57 (GS2). The effect of urea inclusion in foliar Se fertilisers on the penetration rates of Se was also investigated. Wheat was harvested at 3, 10 and 17 d and at 3, 10, and 34 d after Se applications at GS1 and GS2, respectively. Applying foliar Se, irrespective of the formulation, brought grain Se concentration to a level high enough to be considered adequate for biofortification. Inclusion of N in the foliar Se solution applied at an early growth stage increased recoveries in the plants, likely due to improved absorption of applied Se through the young leaves. At a later growth stage, the inclusion of N in foliar Se solutions was also beneficial as it improved the assimilation of applied inorganic Se into bioavailable selenomethionine, which was then rapidly translocated to the grain. Practical knowledge gained about the optimisation of Se fertiliser formulation, method and timing of application will be of importance in refining biofortification programs across different climatic regimes.